2020
DOI: 10.3390/vaccines8030494
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Intramuscular and Subcutaneous Administration of LigA Subunit Vaccine Adjuvanted with Neutral Liposomal Formulation Containing Monophosphoryl Lipid A and QS21

Abstract: Leptospirosis vaccines with higher potency and reduced adverse effects are needed for human use. The carboxyl terminal domain of leptospiral immunoglobulin like protein A (LigAc) is currently the most promising candidate antigen for leptospirosis subunit vaccine. However, LigAc-based vaccines were unable to confer sterilizing immunity against Leptospira infection in animal models. Several factors including antigen properties, adjuvant, delivery system, and administration route need optimization to maximize vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Furthermore, certain formulations of LigAc with alhydrogel failed to induce adequate protection ( Lucas et al., 2011 ; Hartwig et al., 2014 ). LigAc antigen formulated into liposomes or poly-lactic-co-glycolic acid (PLGA) microspheres ( Faisal et al., 2009 ), or formulated with adjuvants including xanthan gum ( Bacelo et al., 2014 ), Salmonella flagellin (FliC) ( Monaris et al., 2015 ), and LMQ, which are neutral liposomes containing a monophosphoryl lipid A (MPL) and a purified saponin fraction from Quillaja saponaria (QS21) ( Techawiwattanaboon et al., 2020 ), showed promoting survival against lethal challenges. However, none of these adjuvanted vaccine formulations completely prevented Leptospira renal colonization ( Faisal et al., 2009 ; Bacelo et al., 2014 ; Monaris et al., 2015 ; Techawiwattanaboon et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, certain formulations of LigAc with alhydrogel failed to induce adequate protection ( Lucas et al., 2011 ; Hartwig et al., 2014 ). LigAc antigen formulated into liposomes or poly-lactic-co-glycolic acid (PLGA) microspheres ( Faisal et al., 2009 ), or formulated with adjuvants including xanthan gum ( Bacelo et al., 2014 ), Salmonella flagellin (FliC) ( Monaris et al., 2015 ), and LMQ, which are neutral liposomes containing a monophosphoryl lipid A (MPL) and a purified saponin fraction from Quillaja saponaria (QS21) ( Techawiwattanaboon et al., 2020 ), showed promoting survival against lethal challenges. However, none of these adjuvanted vaccine formulations completely prevented Leptospira renal colonization ( Faisal et al., 2009 ; Bacelo et al., 2014 ; Monaris et al., 2015 ; Techawiwattanaboon et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, while comparing intramuscular and subcutaneous vaccination of a recombinant leptospirosis vaccine rLigAc formulated with liposome-based adjuvant (LMQ), it has been demonstrated that intramuscular vaccination did not only elicit faster antibody production but also protected from kidney damage following leptospiral infection with better performance than subcutaneous immunization. However, both tested routes did not influence protective efficacy in terms of survival rate and the level of renal colonization [33]. In another phase II clincal trial of a novel amyloid beta synthetic peptide vaccine UB-311 for Alzheimer's disease (AD), the vaccine comprises two amyloid beta targeting peptides, each peptide synthetically linked to different helper T-cell peptide epitopes and formulated in an alum-containing Th2-biased solution, mixed with polyanionic CpG-ODN to form stable immunostimulatory complexes of microsize particulates.…”
Section: ) Intramuscular Routementioning
confidence: 83%
“…In general, PLGA particles cause a Th1 bias in the immune response ( 136 ), although splenic Th1 and Th2 cytokine mRNAs were both increased following immunization with the LigA7’-13/PLGA particles relative to transcript levels from hamsters immunized with LigA7’-13/Al(OH) 3 ( 106 ). In another study, neutral liposomes were mixed with the saponin QS-21 and the TLR4 agonist monophosphoryl lipid A ( 120 , 121 ). 60% of the immunized hamsters survived challenge, whereas no animals immunized with adjuvant alone survived ( 121 ).…”
Section: Vaccine Studiesmentioning
confidence: 99%
“…In another study, neutral liposomes were mixed with the saponin QS-21 and the TLR4 agonist monophosphoryl lipid A ( 120 , 121 ). 60% of the immunized hamsters survived challenge, whereas no animals immunized with adjuvant alone survived ( 121 ). Altering the physicochemical properties of the liposome such as its surface charge or size may substantially improve performance of liposome-based vaccines ( 137 ).…”
Section: Vaccine Studiesmentioning
confidence: 99%
See 1 more Smart Citation